ANALISIS PERBANDINGAN PENDIDIKAN KARAKTER ANTARA NOVEL LASKAR PELANGI DENGAN NOVEL 9 SUMMER 10 AUTUMNS - Ellya Vivi Helmalia; Yesi Nur Wulansari; Wildania Maulidha; Rian Damariswara (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to examine the comparison of character education values between the novel Laskar Pelangi and the novel 9 Summer 10 Autumns. The research uses a qualitative approach with a content analysis method. Data collection was carried out using test instruments. The results of this study show that the two novels have similar plots and show that the two novels both tell about struggles from childhood to adulthood to achieve their dreams. Both novels also share the educational value of the characters we researched. The value of character education that we examined in these two novels is on the value of honesty, religious value, tolerance value, discipline value, and hard work value. As a suggestion, both novels are very good to read because they contain the story of children's struggle to achieve their dreams to be successful in the future. These two novels are very inspiring and can foster a sense of enthusiasm, never give up, tolerance, religious observance, loyal friends, cooperation and hard work in living daily life. For the rest more in-depth research needs to be done